Metastable growth regime for carbon nanowalls and carbon nanofibers in an Ar/H2/C2H2 radiofrequency plasma jet. (16th October 2020) - Stoica, S D; Vizireanu, S; Luculescu, C R; Mitu, B; Dinescu, G
Abstract: We reveal a metastable growth regime during deposition of carbon nanomaterials by PECVD in Ar/H2 /C2 H2 plasma, characterized by a spontaneous transition of the material morphology from carbon nanofibers (CNF) to carbon nanowalls (CNW), during the same continuous experiment, while keeping constant the values of all deposition parameters (radiofrequency power, gas flow rates, pressure, substrate temperature). Thus, one step deposition of layered architectures consisting of CNW standing on the top of CNF is demonstrated. The peculiarities of the transition in the growth regime, from CNF to CNW are not known. Thus, in this study the plasma characteristics leading to single CNW layers are compared to those leading to CNW onto CNF layered architectures. Mass spectrometry is the main investigation method, confirming that comparing to single layer CNW deposition, the metastable growth proceeds at increased ratios of hydrogen ions to carbon clusters ions.